2021
DOI: 10.3390/pediatric13020026
|View full text |Cite
|
Sign up to set email alerts
|

Triple Atresia, Triple Threat? An Unusual Constellation of Primary Surgical Abnormalities

Abstract: We present a case series of two patients with tracheo-oesophageal fistula with oesophageal atresia (TOF/OA), duodenal atresia (DA) and ano-rectal malformation (ARM). This constellation of abnormalities, dubbed triple atresia (TA), is a rare combination with few described cases in the literature. Here we describe our management of these cases, as well as the results of our literature review. Both of our cases had staged surgical procedures and were initially managed with thoracotomy for repair of TOF/OA on day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Raef et al favor staged surgery over single-staged surgery as it is found to have a better survival rate. [1] As outlined in table 1, only one mortality was documented among the staged group. However, as of now, there is no clear guideline available for managing triple atresia as the anomaly remains extremely rare.…”
Section: Dear Sirmentioning
confidence: 94%
See 2 more Smart Citations
“…Raef et al favor staged surgery over single-staged surgery as it is found to have a better survival rate. [1] As outlined in table 1, only one mortality was documented among the staged group. However, as of now, there is no clear guideline available for managing triple atresia as the anomaly remains extremely rare.…”
Section: Dear Sirmentioning
confidence: 94%
“…However, as of now, there is no clear guideline available for managing triple atresia as the anomaly remains extremely rare. [1][2][3] As to the sequence of staged surgery, we opted to perform TEF repair first as there is a risk of gastric distension due to air venting down from the trachea into the stomach through distal fistula which can also cause gastric perforation. [4] Both Raef and Spitz et al suggest that performing TEF repair as the first surgery yields a better outcome.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of oesophageal atresia ranges from 1 in every 2500 to 4500 live births [ [1] , [2] , [3] ]. Oesophageal atresia is associated with several major complications, the most prevalent being the VACTERL association, wherein the incidence of oesophageal atresia is notably elevated (50–80 %) [ 4 , 5 ]. On the other hand, duodenal atresia has been described in patients presenting with a collection of anomalies consistent with VACTERL [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, duodenal atresia has been described in patients presenting with a collection of anomalies consistent with VACTERL [ 6 ]. Particularly, congenital duodenal atresia is estimated to be present in approximately 3–6 % of neonates with oesophageal atresia, whether accompanied by a tracheoesophageal fistula (TEF) or not [ 5 , [7] , [8] , [9] ]. Furthermore, duodenal atresia has been observed with oesophageal atresia and anorectal malformations.…”
Section: Introductionmentioning
confidence: 99%